2023
DOI: 10.1111/bjhp.12661
|View full text |Cite
|
Sign up to set email alerts
|

How the COVID‐19 crisis affected the well‐being of nurses working in paediatric critical care: A qualitative study

Abstract: ObjectivesEvidence shows paediatric critical care (PCC) nurses display high rates of burnout, moral distress, symptoms associated with post‐traumatic stress disorder (PTSD) and poor well‐being. The COVID‐19 pandemic magnified these pressures producing extremely challenging working conditions. The objective was to understand PCC nurses' lived experience of working during COVID‐19 to determine the impact it had on their well‐being.DesignA qualitative design was used with individual, semi‐structured online interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Results may not transfer to other sites or countries but it clearly resonates internationally. 30,55,56 Further research in other countries would help confirm this transferability.…”
Section: Limitationsmentioning
confidence: 78%
See 1 more Smart Citation
“…Results may not transfer to other sites or countries but it clearly resonates internationally. 30,55,56 Further research in other countries would help confirm this transferability.…”
Section: Limitationsmentioning
confidence: 78%
“…54 These are described as basic psychological needs for psychological growth and well-being. 44 Previous research with PCC staff corroborated this theory 30,55 and these concepts were identified in a recent British Medical Association (BMA) report to represent the A-B-C of well-being in medical practice 29 : autonomy/control, belonging and competence.…”
Section: Discussionmentioning
confidence: 88%
“…We targeted newly qualified nurses (who worked for less than 5 years as a registered nurse) because existing evidence 18 had suggested that they may struggle more with their well-being than senior colleagues. Equally, we were interested to explore the experiences of senior nurses working as advanced nurse practitioners or well-being leads because they had taken on roles to support others’ well-being.…”
Section: Methodsmentioning
confidence: 99%
“…In pediatric nurses, pandemic-era research mirrored concerns expressed by the general nursing workforce. However, the pediatric nurse experience revealed additional considerations related to family-centered care, restrictions in (parent and family) visitation, pediatric nurses’ fear, and difficulty transitioning to care for adult patients with COVID-19 [ 65 , 66 , 67 ]. The disruption of family-centered care directly resulted from visiting restrictions on parents, siblings, friends, and extended family members [ 68 , 69 , 70 , 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the pandemic, pediatric nurses in a variety of settings reported or met criteria for anxiety, depression, perceived stress, and psychological distress [ 73 , 74 ]. Burnout and poor quality of life resulted from caring for pediatric patients during the pandemic [ 67 , 75 , 76 ]. Pediatric nurses and other healthcare workers have described excessive workload due to co-worker illnesses, staffing shortages, patient acuity, and high patient volumes [ 41 , 67 ].…”
Section: Introductionmentioning
confidence: 99%